UJI KANDUNGAN TIMBAL (Pb) PADA GORENGAN YANG DIJUAL DI PINGGIR JALAN SEPANJANG PANTAI GANDORIAH PARIAMAN SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Yulia, Mega; Syahrianti, Dani; Yulis, Rahma (Jurnal Riset Kefarmasian Indonesia, 2021)
Lead is one of the heavy metal elements found in the air pollution which is produced together with motor vehicle fumes. Lead can cause various disorders in human body such as anemia, neurological damage, deformities and body functions, dental caries, impaired kidney function, effects on the heart and infertility. Lead can enter the human body through inhaled air, through the skin and ingested with food. The purpose of this study was to determine the lead content in fried foods (fried sala, fried crab, fried shrimp and fried fish) sale around of Gandoriah Beach, Pariaman. This research was conducted at Baristand Laboratory (Research and Standarirdization Industry Center) Padang from February until March 2020. This study was conducted on 4 samples taken randomly from the total population. The instrument used was atomic absorption spectrophotometry (AAS). The results of 4 samples showed that the lead content in fried sala was 0.1618 mg/kg, with a maximum SNI limit is 0.3 mg/kg, fried crab was 0.4025 mg/kg with a maximum SNI limit is 0,5 mg/kg, fried shrimp was 0.4377 mg/kg with a maximum SNI limit is 0.5 mg/kg, fried fish was 0.2331 mg/kg with an SNI maximum limit is 0.3 mg/kg. Based on the results of this study, it can be concluded all samples contain lead but the level is still below of maximum limit of SNI 7387-2009.